2012
DOI: 10.1111/j.1365-2494.2012.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation and selection of traits related to forage yield in tall fescue under irrigated and drought stress environments

Abstract: Development of a standard evaluation protocol has been a pressing problem for the selection of drought‐resistant genotypes of tall fescue (Festuca arundinacea). This study was conducted to evaluate the association of forage yield with specific phenological and morphological traits to find a proper model for indirect selection under irrigated (normal) and drought‐stress conditions in tall fescue. A random sample of seventy‐five genotypes were clonally propagated and evaluated in normal and drought‐stress enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 39 publications
(48 reference statements)
9
40
0
3
Order By: Relevance
“…The most convenient way to assess the heritability of a trait is to use clonal material, which is easily obtained in many forage plants by splitting a plant into ramets of one or more tillers. In the present study, estimation of broad-sense heritability for DMY (h 2 = 0.21-0.29) and LSR (h 2 = 0.3) were almost similar to the estimates by Julier et al (2000) in alfalfa, Ebrahimiyan et al (2012) in tall fescue, and Araghi et al (2014) in smooth bromegrass (Bromus inermis). On the basis of clonal material, variances can be estimated and used to calculate heritability (Wricke and Weber, 1986;Nyquist, 1991).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The most convenient way to assess the heritability of a trait is to use clonal material, which is easily obtained in many forage plants by splitting a plant into ramets of one or more tillers. In the present study, estimation of broad-sense heritability for DMY (h 2 = 0.21-0.29) and LSR (h 2 = 0.3) were almost similar to the estimates by Julier et al (2000) in alfalfa, Ebrahimiyan et al (2012) in tall fescue, and Araghi et al (2014) in smooth bromegrass (Bromus inermis). On the basis of clonal material, variances can be estimated and used to calculate heritability (Wricke and Weber, 1986;Nyquist, 1991).…”
Section: Discussionsupporting
confidence: 82%
“…The highest PH, IL, NS, NN, DMY, LSR, ProC, and RWC were observed for ecotype 8, which belongs to Baft in Kerman province of Iran. Ebrahimiyan et al (2012) showed that water stress had a negative effect on forage yield and many of the morphological traits in tall fescue (Festuca arundinacea) and reduced the genotypic variation for most of the traits. The lowest NS and DMY were observed for ecotypes 1 (Arak), 3 (Semirom), and 4 (Sanandaj), which belong to cold regions of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Tall fescue is not only more drought resistant than Lp, but it also has a higher yield potential (Wilman and Gao, ; Pontes et al ., ; Gilliland et al ., ; Van Eekeren et al ., ). These attributes of tall fescue are being increasingly recognized as an adaptation to moisture stress not only in Europe (Reheul et al ., ) but also in other regions (Scheneiter and Améndola, ; Turner et al ., ; Ebrahimiyan et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…These findings broadly support those of multiple earlier studies (Singh and Sen 2000;Singh and Kumar 2008;Pal and Kumar 2010), although the heritability of individual traits was not entirely consistent with the findings of these other studies. Several reports have suggested that trait heritability is not a constant but may vary according to the environmental conditions (Alza and Fernandez-Martinez 1997;Andalo et al 1998;Galloway 2001;Agrawal 2002;Galloway and Etterson 2007;Riginos et al 2007;Ebrahimiyan et al 2013). Thus, plant phenotypes appeared to be significantly influenced by the levels of light, nutrients, water, temperature and CO 2 , or by herbivore pressures (Bossdorf et al 2009).…”
Section: Estimation Of Heritability Within T Patulamentioning
confidence: 92%